1998
DOI: 10.1159/000025351
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Phage Specific to Hemorrhagic <i>Escherichia coli&nbsp; </i>O157:H7 and Disclosure of Variations in Host Outer Membrane Protein OmpC

Abstract: Phage AR1, previously known to infect Escherichia coli O157:H7 with high specificity, was further characterized for its genetic properties. The phage DNA sequences including capsid genes and a putative α-glucosyltransferase gene (α-gt) have been deduced. These sequences are conservative but not identical to those of T4 phage. However, a nonessential gene, SegD, organized within the capsid gene cluster of T4 is missing in the corresponding region of AR1 genome, and this characteristic has not been observed amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…Similar to the case with T4 and other T4-like phages, restric-tion enzyme digestion experiments suggested that the AR1 genome is highly modified to protect it from restriction enzyme digestion by the host defense system (89). Partial sequencing data (ϳ10 kb) of AR1 indicated that AR1 has several structural genes that are highly similar to T4 genes (17,37,89).…”
mentioning
confidence: 65%
See 4 more Smart Citations
“…Similar to the case with T4 and other T4-like phages, restric-tion enzyme digestion experiments suggested that the AR1 genome is highly modified to protect it from restriction enzyme digestion by the host defense system (89). Partial sequencing data (ϳ10 kb) of AR1 indicated that AR1 has several structural genes that are highly similar to T4 genes (17,37,89).…”
mentioning
confidence: 65%
“…All of the E. coli strains were cultured at 37°C in Luria-Bertani broth with agitation (180 rpm). AR1 phage were propagated in E. coli O157:H7 strain 1266 as described previously (70,89). E. coli phages T4 and RB69, obtained from J. D. Karam (Tulane University), were propagated in E. coli strain B E (92).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations